(untitled) (Pedagogical Cluster-Journal of Pedagogical Developments, 2024)
The main purpose of preparing financial statements is to increase the interest of investors, creditors and other users. Based on the Decision of our Honorable President No. 4611 of February 14, 2020, it is established that financial statements must be prepared based on international standards. [1]. Subsidiaries of large tax-paying organizations determine that the financial statements of the parent company must be compiled in a consolidated form in order to prepare annual financial reporting forms. As a result, the parent company collects the financial reports of the subsidiaries and prepares consolidated financial statements by collecting quarterly and annual reports.